2019
DOI: 10.1002/path.5284
|View full text |Cite|
|
Sign up to set email alerts
|

NR4A3 fusion proteins trigger an axon guidance switch that marks the difference between EWSR1 and TAF15 translocated extraskeletal myxoid chondrosarcomas

Abstract: Extraskeletal myxoid chondrosarcoma (EMC) is a rare sarcoma histotype with uncertain differentiation. EMC is hallmarked by the rearrangement of the NR4A3 gene, which in most cases fuses with EWSR1 or TAF15. TAF15‐translocated EMC seem to feature a more aggressive course compared to EWSR1‐positive EMCs, but whether the type of NR4A3 chimera impinges upon EMC biology is still largely undefined. To gain insights on this issue, a series of EMC samples (7 EWSR1‐NR4A3 and 5 TAF15‐NR4A3) were transcriptionally profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
0
24
0
2
Order By: Relevance
“…Recently, it was reported that EWSR1 - and TAF15 -translocated EMCs feature a different transcriptional profile, with the axon guidance pathway being a major discriminant. In particular, compared to the EWSR1-NR4A3 EMC subtype, TAF15-NR4A3 EMC over-expresses pro-tumorigenic axonal guidance molecules, supporting the notion that the type of NR4A3 partner dictates an axon guidance switch that affects tumor biology [ 35 ]. These findings are in agreement with some reports suggesting that TAF15-NR4A3 EMC features a more aggressive phenotype, with a high-grade morphology and plasmocytoid/rhabdoid morphology in over half of TAF15 -translocated EMCs [ 36 ].…”
Section: Diagnostic Criteriamentioning
confidence: 77%
See 2 more Smart Citations
“…Recently, it was reported that EWSR1 - and TAF15 -translocated EMCs feature a different transcriptional profile, with the axon guidance pathway being a major discriminant. In particular, compared to the EWSR1-NR4A3 EMC subtype, TAF15-NR4A3 EMC over-expresses pro-tumorigenic axonal guidance molecules, supporting the notion that the type of NR4A3 partner dictates an axon guidance switch that affects tumor biology [ 35 ]. These findings are in agreement with some reports suggesting that TAF15-NR4A3 EMC features a more aggressive phenotype, with a high-grade morphology and plasmocytoid/rhabdoid morphology in over half of TAF15 -translocated EMCs [ 36 ].…”
Section: Diagnostic Criteriamentioning
confidence: 77%
“…Although the precise mechanism behind the selective activity of antiangiogenics in EMC is still undefined, the transcriptional profiling of a subset of responder and non-responder EMCs highlighted up-regulation of canonical pazopanib targets FMS-lyke tyrosine kinase 1 (FLT1/vascular endothelial growth factor receptor 1-VEGFR1), kinase insert domain receptor (KDR/vascular endothelial growth factor receptor 2-VEGFR2), FMS-lyke tyrosine kinase receptor 4 (FLT4/vascular endothelial growth factor receptor 3-VEGFR3), and cognate ligands (vascular endothelial growth factor A-VEGFA and vascular endothelial growth factor C-VEGFC), as well as components of the Notch Homolog Protein (NOTCH) pathway in the pazopanib-sensitive cohort. Intriguingly, as observed with sunitinib, all three TAF15-NR4A3 -positive tumors included in this pazopanib trial failed to respond to pazopanib, which suggests that the more malignant phenotype of the TAF15-translocated EMC may impair antiangiogenic sensitivity [ 35 ]. Eventually, a retrospective study of apatinib, a new selective inhibitor of VEGFR2 under investigation in different cancers, among which is STS, identified one partial response and two stable diseases of three EMC patients, with an interesting median duration of response of 21.2 months [ 61 ].…”
Section: State Of the Art: Advanced Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Leiomyosarcoma was associated with deletion of TP53 and RB1 gene and BRCA1/2 gene rearrangement [48]. EMC was correlated with NR4A3 gene rearrangement [46]. Chordoma was associated with T-boxfamily transcription factor; brachyury [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have only been a few previous reports about the association between smoking and sarcoma development [22][23][24][25][26]42]. Recent genomic studies have expanded our knowledge regarding the basis of carcinogenesis, including sarcoma; however, gene abnormalities, such as fusion genes or driver mutations, in most types of sarcoma remain unclear [43][44][45][46][47][48][49][50]. Understanding the impact of lifestyle habits, lifestyle diseases, and genetic abnormalities would be helpful to advise patients on how to prevent carcinogenetic factors and also how to obtain appropriate genetic counseling.…”
Section: Discussionmentioning
confidence: 99%